Determining the Main Priority in the Assessment of Hollywood Horror Films by Applying the AHP and SAW Methods - Hasibuan, Muhammad Siddik; Irawan, Muhammad Dedi; Pratama, Dian Agus; Yudhistira, Yudhistira (International Conference on Sciences Development and Technology, 2021)
Film is one of the many modern communication media that is very effective to be used as a medium of entertainment as well as a place to convey moral messages that can influence the audience both from the aspect of attitude, point of view of thought and also insight. For this reason, the production house is required to continue to create a film of the highest quality. Because the proliferation of these types of horror films makes it difficult for viewers to determine which Hollywood horror film is the best version, this is also one of our goals in designing a web-based system. In this case study, the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods are used to determine the best priority for each alternative assessment. The assessment procedure is based on predetermined criteria. The criteria used as assessment provisions are budget, film duration, audience rating, film rating, film awards and film revenues. The method used is to compare the AHP and SAW methods as well as the results of calculations from the system. The results of the discussion include the stages of assessment and comparison of each method used and are able to appoint the best alternative in the selection of Hollywood horror films.